ADSORPTION OF EU3+ TO SMECTITES AND FLUORO-TETRASILICIC MICA - Okada T.; Ehara Yu.; Ogawa M. (My University, 2007)
The adsorption of Eu3+ from aqueous solution to natural Na+-montmorillonite (Kunipia F), synthetic saponite (Sumecton SA) and synthetic fluoro-tetrasilicic mica (Na+-TSM) clay samples was investigated. Adsorption capacities derived from the isotherms were 1.02, 0.71 and 1.00 meq/g of clay, respectively, for Kunipia F, Sumecton SA and Na+-TSM. The adsorption capacities were comparable to the cation exchange capacities of the clays, which were 1.19, 0.71 and 0.94 meq/g of clay, respectively. The greater slope of the TSM adsorption isotherm relative to the montmorillonite and saponite isotherms indicates a high affinity of Eu3+ for Na+-TSM. The high affinity of TSM for Eu3+ was thought to be related to the large electronegativity of the octahedral fluorine groups in TSM. Photoluminescence of adsorbed Eu3+ was observed for saponite and TSM, but not for montmorillonite. Quenching of Eu3+ luminescence by Fe in the montmorillonite structure is the probable reason for this phenomenon. The luminescence intensity varied with the amount of adsorbed Eu3+ for saponite and TSM as a result of self-quenching.
Keywords: ADSORPTION; EUROPIUM (III) ION; FLUOROTETRASILICIC MICA; KUNIPIA F; MONTMORILLONITE; PHOTOLUMINESCENCE; SUMECTON SA; SYNTHETIC SAPONITE